1988
DOI: 10.1007/bf01245140
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-derived alkaloids in alcoholism and in Parkinson's and Huntington's diseases

Abstract: Tetrahydroisoquinoline (TIQ) alkaloids and 1-carboxy TIQ derivatives have been found in human fluids and/or tissues. The possible biosynthetic pathways of salsolinol (Sal), taken as an example of TIQs, are discussed, and the possibility that biosynthesis occurs through a stereospecific enzymatic reaction is considered. In this respect, it is reported that the R enantiomer of Sal predominates in urines of healthy volunteers, whereas the S enantiomer predominates in port wine and possibly in other beverages and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 40 publications
(35 reference statements)
1
23
0
Order By: Relevance
“…3 5 ) to that of Sal found in port wine. 4 Our result suggests that in oioo formation of 1 MeTIQ proceeds via an enzymatically assisted reaction, but details of the biosynthetic route of lMeTIQ are at this time unclear. We found significantly decreased concentrations of lMeTIQ in the frontal lobe of parkinsonians compared to controls.'…”
Section: Discussionmentioning
confidence: 88%
“…3 5 ) to that of Sal found in port wine. 4 Our result suggests that in oioo formation of 1 MeTIQ proceeds via an enzymatically assisted reaction, but details of the biosynthetic route of lMeTIQ are at this time unclear. We found significantly decreased concentrations of lMeTIQ in the frontal lobe of parkinsonians compared to controls.'…”
Section: Discussionmentioning
confidence: 88%
“…The selective transport of (R)-I,2-DiMeDHTIQ by dopamine transporter, intracellular oxidation into more cyctotoxic ion, and the accumulation may be the most important mechanism underlying the neurotoxicity of 1,2-DiMeDHTIQ to dopaminergic neurons. (S)-I-MeDHTIQ occurs in some foods, such as port wine (Dostert et al, 1988), but it cannot pass through the blood-brain barrier (Origitano et al, 1981), indicating that 1-MeDHTIQ found in the brain should be the (R)-enantiomer synthesized in situ (Dostert et al, 1990). From their different origins, biological activity of the (R)-and (S)-enantiomer of 1-MeDHTIQ and their N-methylated derivatives has been suggested to differ each other.…”
Section: Discussionmentioning
confidence: 98%
“…1-MeDHTIQ is synthesized in the brain by condensation of dopamine with pyruvic acid, followed by decarboxylation and possibly enzymatic reduction, which yields the (R)-enantiomer under physiological conditions (Dostert et al, 1990;Strolin Benedetti et al, 1989). In the urine of healthy human controls, only (R)-I-MeDHTIQ was detected (Dostert et al, 1990), while the (S)-enantiomer is dominant in wine and other foods (Dostert et al, 1988). When the concentration of dopamine or acetalcehyde increases, as in the patients treated with L-DOPA or of alcoholism, both (R)-and (S)-I-MeDHTIQs are supposed to be synthesized by nonenzymatic Pictet-Spengler reaction of dopamine with acetaldehyde.…”
Section: Introductionmentioning
confidence: 97%
“…1,2-Dehydrosalsolinol has been reported to be a potent inhibitor of catechol-O-methyltransferase (Cheng et al, 1987) Its increased formation after administration of Madopar might contribute to the beneficial effects of L-dopa therapy by inhibiting one of the catabolic pathways of DA. Thus, 1,2-dehydrosalsolinol should be considered as one of the dopamine-derived alkaloids which may play a role in pathological situations, such as alcoholism and Parkinson's disease (Sourkes, 1971;Dostert et al, 1988).…”
Section: Discussionmentioning
confidence: 99%